CONFLICT RESOLUTION PATTERNS IN INDIGENOUS COMMUNITIES OF INDONESIA: A COMPREHENSIVE STUDY OF THE CUSTOMARY LAWS OF BADUY, KAJANG, AND ANAK DALAM IN JAMBI - Rena Yulia; Chairul Huda; Muhamad Romdoni; Achmad Cholidin; Bhanu Prakash Nunna (Faculty of Law, Universitas Lampung, 2025)
This study examines the conflict resolution practices of Baduy, Kajang, and Suku Anak Dalam (SAD) Jambi communities, all of whom continue to apply customary law to address violations within their territories. Using a combination of normative and empirical methods with snowball data collection, the research identifies the traditional mechanisms through which these communities maintain social order. Baduy resolve disputes through Silih Hampura, carried out via the Ngabokoran process and guided by Pikukuh, an unwritten code defining customary violations and their resolutions. Kajang apply Pasang Ri Kajang, an oral system that uses oaths, crowbar-burning, or incense-burning rituals in conflict settlement. The SAD Jambi follow a customary framework consisting of four primary and four secondary principles and dua belas categories of violations. Conflict resolution in Kajang and SAD communities typically involves customary fines, while the Baduy impose banishment rather than imprisonment. Across the three groups, the central aim of customary dispute resolution is the restoration of cosmic religious balance, benefiting not only the parties involved but the community and the wider natural order.